Ship of Theseus - Gandhi, Anand; Al-Khashef, Aida; Kabi, Neeraj; Shah, Sohum; Shukla, Vinay (New Delhi : Eagle Home Entertainment, 2013)
The film explores questions of identity, justice, beauty, meaning and death through the stories of an experimental photographer, an ailing monk and an enterprising stockbroker
English subtitles
Keywords: Monks; Stockbrokers; Blind Drama